A molecular link between Hairless and Pros26.4, a member of the AAA-ATPase subunits of the proteasome 19S regulatory particle in Drosophila - Müller, Dominik; et al. (Journal of Cell Science, 2006)
The proteasome is the major degradation machinery of the cell that regulates multiple cellular processes as diverse as cell cycle, signal transduction and gene expression. Recognition and unfolding of target proteins involves the regulatory cap whose base contains six AAA-ATPases that display reverse chaperone activity. One of them, Rpt2 (also known as S4), has an essential role in gating the degradative central core. We have isolated the orthologous gene Pros26.4 from Drosophila melanogaster as a molecular interaction partner of Hairless. Hairless plays a major role as antagonist of Notch signalling in Drosophila, prompting our interest in the Hairless-Pros26.4 interaction. We find that Pros26.4 negatively regulates between Hairless at the genetic and molecular level. Depletion of Pros26.4 by using tissue-specific RNA interference (RNAi) resulted in a specific stabilization of the Hairless protein, but not in stabilization of the intracellular domain of Notch or the effector protein Suppressor of Hairless. Thus, the Hairless-Pros26.4 interaction provides a novel mechanism of positive regulation of Notch signalling.
Keywords: Drosophila; hairless; notch regulation; Pros26.4; protein stability